Identification of UL69 Gene and Protein in Cytomegalovirus-Transformed Human Mammary Epithelial Cells - Haidar Ahmad, Sandy; Al Moussawi, Fatima; El Baba, Ranim; Nehme, Zeina; Pasquereau, Sébastien; Kumar, Amit; Molimard, Chloé; Monnien, Franck; Algros, Marie-Paule; Karaky, Racha; Stamminger, Thomas; Diab Assaf, Mona; et al. (Frontiers in Oncology, 2021)
A growing body of evidence addressing the involvement of human cytomegalovirus (HCMV) in malignancies had directed attention to the oncomodulation paradigm. HCMV-DB infected human mammary epithelial cells (HMECs) in culture showed the emergence of clusters of rapidly proliferating, spheroid-shaped transformed cells named CTH (CMV-Transformed HMECs) cells. CTH cells assessment suggests a direct contribution of HCMV to oncogenesis, from key latent and lytic genes activating oncogenic pathways to fueling tumor evolution. We hypothesized that the presence of HCMV genome in CTH cells is of pivotal importance for determining its oncogenic potential. We previously reported the detection of a long non-coding (lnc) RNA4.9 gene in CTH cells. Therefore, we assessed here the presence of UL69 gene, located nearby and downstream of the lncRNA4.9 gene, in CTH cells. The HCMV UL69 gene in CTH cells was detected using polymerase chain reaction (PCR) and sequencing of UL69 gene was performed using Sanger method. The corresponding amino acid sequence was then blasted against the UL69 sequence derived from HCMV-DB genome using NCBI Protein BLAST tool. A 99% identity was present between the nucleotide sequence present in CTH cells and HCMV-DB genome. UL69 transcript was detected in RNA extracts of CTH cells, using a reverse transcription polymerase chain reaction (RT-PCR) assay, and pUL69 protein was identified in CTH lysates using western blotting. Ganciclovir-treated CTH cells showed a decrease in UL69 gene detection and cellular proliferation. In CTH cells, the knockdown of UL69 with siRNA was assessed by RT-qPCR and western blot to reveal the impact of pUL69 on HCMV replication and CTH cell proliferation. Finally, UL69 gene was detected in breast cancer biopsies. Our results indicate a close link between the UL69 gene detected in the HCMV-DB isolate used to infect HMECs, and the UL69 gene present in transformed CTH cells and tumor biopsies, further highlighting a direct role for HCMV in breast tumor development.